Primary chemo-radiotherapy for breast cancer patients who refused surgical treatment: a case series - Kao, Patrick; Chi, Mau-Shin; Chi, Kwan-Hwa; Ko, Hui-Ling (Therapeutic Radiology and Oncology, 2019)
Mastectomy or breast conserving surgery (BCS) followed by adjuvant radiotherapy (RT) and/or chemotherapy plus hormone therapy is the current standard of care for breast cancer (BC). The disease usually progresses in patients who refuse any form of surgical intervention and notoriously impacts their life expectancy and quality. We collected 5 BC patients who refused any form of surgery and who received definitive RT or RT with chemotherapy (CCRT). The staging included early stage to locally advanced BCs according to criteria of the American Joint Committee on Cancer (AJCC) version 7. All patients achieved good local control. Only one had recurrence and was successfully salvaged by re-irradiation. The cosmetic effects were all satisfactory. Primary CCRT for BC patients who refuse surgery can be an effective alternative for achieving good survival and maintaining good quality of life.